上式等于
(1减1/2减1/3…负1/2008)×(1/2+1/3+1/4+…+1/2008)
+(1减1/2减1/3…负1/2008)×(1/2009)
-(1减1/2减1/3减…负1/2008)×(1/2+1/3+1/4+…+1/2008)
-(1/2+1/3+1/4+…+1/2008)×(-1/2009)
即等于
(1减1/2减1/3…负1/2008)×(1/2009)
-(1/2+1/3+1/4+…+1/2008)×(-1/2009)
即等于
[(1减1/2减1/3…负1/2008)+(1/2+1/3+1/4+…+1/2008)]×(1/2009)
等于0
(1减1/2减1/3…负1/2008)=1-(1/2+1/3+1/4+…+1/2008)
(1减1/2减1/3减…负1/2009)=1-((1/2+1/3+1/4+…+1/2009))
代入
(1减1/2减1/3…负1/2008)×(1/2+1/3+1/4+…+1/2009)-(1减1/2减1/3减…负1/2009)×(1/2+1/3+1/4+…+1/2008)
=【1-(1/2+1/3+1/4+…+1/2008)】×(1/2+1/3+1/4+…+1/2009)-【1-((1/2+1/3+1/4+…+1/2009)】(1/2+1/3+1/4+…+1/2008)
=(1/2+1/3+1/4+…+1/2009)-(1/2+1/3+1/4+…+1/2008)
=1/2009
我来
设 1/2 + 1/3 +1/4 + ---- + 1/2008 为X
则原题可以化为=
(1-X)(X+1/2009)-(1-X-1/2009)X
然后算出来
我先把这个拆开来= X + 1/2009 - X的平方 - 1/2009X - X+ X的平方 + 1/2009X
也就是= 1/2009
给我分吧
牛,我做好一看就那么多人了
设1减1/2减1/3…负1/2008=a,1/2+1/3+1/4+…+1/2008=b
(1减1/2减1/3…负1/2008)×(1/2+1/3+1/4+…+1/2009)-(1减1/2减1/3减…负1/2009)×(1/2+1/3+1/4+…+1/2008)
=a×(b+1/2009)-(a-1/2009)×b
=ab+a*1/2009-ab+b*1/2009
=(a+b)*1/2009
=(1减1/2减1/3…负1/2008+1/2+1/3+1/4+…+1/2008)*1/2009
=1/2009
设1减1/2减1/3…负1/2008=A 1/2+1/3+1/4+…+1/2008)=B
A(B+1/2009)-(A-1/2009)B
=(A+B)/2009
=1/2009